Pengaruh Fasilitas Kerja Terhadap Kinerja Pada Guru SMPN 8 Kota Jambi - Rasdi Rasdi (Universitas Batanghari Jambi, 2021)
SMP 8 Kota Jambi is one of the 25 state junior high schools in Jambi City and has contributed a lot to community education progress programs in the Jambi City area. The population in this study is the number of Teachers of SMPN 8 Kota Jambi which is as many as 60 teachers. Sampling used is a census method that all populations are sampled as many as 60 teachers. The analysis tool used is simple linear regression. Based on the results of the study revealed that there is a positive influence between work facilities on performance in teachers of SMPN 8 Kota Jambi. Thus there is a significant influence between the variables of work facilities on the performance of teachers of SMPN 8 Kota Jambi.